Considerations for decision-making in quality among the main contractor in the construction industry: a case study of the MRT2 elevated project Klang Valley - Md Zin, Nurulhayati; Zainol, Nurul Nadiah; Ahmad Zawawi, Emma Marinie; Mohd Lazi, Mohd Khairul Afzan; Mohd Ismail, Anwar (UiTM Press, 2025)
Decision-making is essential for maintaining quality in large infrastructure projects like the MRT2 Elevated Project in Klang Valley, Malaysia. Decision-making involves gathering information, evaluating options, and making choices that affect time, cost, and quality. This research examines challenges faced by main contractors in decisionmaking related to quality and suggests solutions for better project outcomes. A mixed-method approach was used, including a survey of executive-level contractors and interviews analysed with Atlas.Ti. The research identified twelve key issues under three (3) categories: Top Management, Customer Satisfaction, and Strategic Management Process. It also highlighted eight (8) important factors for effective decision-making: strategic management, clear guidelines, quality assurance and control, regular meetings, effective communication, managing constraints, skilled decision-makers, and continuous training. These findings provide practical solutions to improve quality management, helping.